Thermal conditions of a heat supply object with local heat supply to the working zone from a gas infrared emitter under mixed convection conditions; AIP Conference Proceedings; Vol. 2422 : Heat and mass transfer in the thermal control system of technical and technological energy equipment (HMTTSC 2021) - Borisov B. V. Boris Vladimirovich; Vyatkin A. V. Aleksandr Vitaljevich; Maksimov V. I. Vyacheslav Ivanovich; Nagornova T. A. Tatiana Aleksandrovna (Physical and mathematical modeling of heat and mass transfer under intensive phase transformations, 2021)
Title screen